Impact of the BRT on accessibility to employment opportunities; case of Witsand: Atlantis, Cape Town - Marimira, Sharon Tsitsi (Department of Construction Economics and Management, 2026)
Witsand is a settlement located 40km from Cape Town Civic Centre making it a peripheral area within Cape Town. The community faced social exclusion in that, the area had no direct public transport services linking them to the city centre. They had no train services and had to rely on minibus taxis that connected them to Dunoon and from there interconnected to different areas of employment. As such they also suffered from economic exclusion because they had to pay higher fares as minibus fares charge higher costs than conventional buses. The residents had to endure long commune distances to and from work and consequently spent significant amounts of their time traveling. Cape Town Municipality created “the Bus Rapid Transit (BRT)” system MyCiTi, to help address the inequality issues within the city for low-income settlement. Therefore, the research aimed to evaluate the impact of the BRT on accessibility to employment opportunities for the residents in Witsand, Atlantis in Cape Town. The study is based on Witsand as it met the criterion of being a low-income settlement and being located at the urban fringes of Cape Town. Household surveys, in-person observations, and computer research (Geographical Information Systems, GIS) were used to gather the data for the study. The study shows that, before MyCiTi started to operate in the area, most of the residents restricted their employment areas to local employment opportunities like Atlantis centre, Atlantis industrial and Witsand. Currently, the BRT has provided people with various possibilities to access jobs in the Central Business District or civic centre and other sub-nodes, such as Century City, and Table View because the routes take inhabitants straight to these nodes without the need to interchange to other modes. There has been growth along the northern corridor of Cape Town in residential and commercial activities. MyCiTi fares are more affordable than different options of transportation like Sibanye and minibus taxis, and this has arguably enabled the residents to travel more, to areas of employment and even have multiple jobs. Furthermore, MyCiTi is dependable and safe as the system has reliable bus schedules making it easier for commuters to plan their journeys and be more flexible. However, in terms of travel time, there are no changes from before MyCiTi was developed. This is because the spatial structure of Cape Town encourages long travel distances. The thesis was case based and as such the findings may not be generalisable. The thesis seeks to add to the debate of creating equitable inclusive cities that are accessible for both low- and highincome residents.